Radiation destruction and internal friction in silicon single crystals - Ryzhikov, V.D.; Rokhmanov, N.Ya.; Galkin, S.N.; Gnap, A.K. (Вопросы атомной науки и техники, 2004)
The study of radiation defects in silicon single crystals of different orientation is carried out by means of methods of internal friction (IF) and electrical resistance. At the mechanical damping measurement a strategy of low-frequency flexible oscillations (f ~ 5 Hz) was used during the process of irradiation with α-particles. The descending curves and anomalous inverted hysteresis effect of IF versus amplitude of cyclic deformation were observed. The results were explained by the processes of ionization by induced infra-red radiation and charged dislocation-point defects association interaction.